PEMBELAJARAN HASIL MENULIS TEKS FABEL DENGAN MENGGUNAKAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING - Hapipah, Wina; Wikanengsih, Wikanengsih; Kartiwi, Yesi Maylani (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research was motivated by the results of observations by researchers who encountered obstacles regarding learning to write, one of which was in the fable text, because the difficulty level of expressing ideas in fables was considered higher than in other texts. The information is taken from the results of pre-research conducted with field observations. Therefore, this study formulated a problem that was carried out using a problem-based learning learning model. From this formulation, the researcher had a specific goal regarding the impact of writing fable text skills on the aspect of value evaluation, which aims to improve students' writing skills. During the process, the problem-based learning model is implemented in groups of 4-5 students so that students can exchange ideas in a structured manner.The method used in this study combines qualitative description with data collection techniques in the form of writing skills involving five aspects, namely, content, structure, linguistic rules, EBI, and writing. The object of the research is 31 grade VII students at SMPN 1 Cihampelas. The data collection technique was by taking writing skills test data and paying attention to five aspects, namely content, structure, linguistic rules, EBI, and writing. By using a problem-based learning model that is systematically arranged to achieve the learning objectives to be achieved and a learning method that is able to assist the learning process and can facilitate students in discussing in groups about writing fable texts, The results of this study showed that 4 students got the highest score and 27 students got a sufficient score with an average value of 88.9, so it can be concluded that the use of the problem-based learning learning model in learning to write fable texts is effectively used in class VII 7 students.